An Applicable Inflammation-Joined and Nutrition-Related Prognostic Indicator in Patients With Colorectal Cancer - Wu, Guo; Liu, Jungang; Liu, Haizhou; Jin, Lan; Huang, Xiaoliang; Mo, Xianwei; Zhong, Huage; Li, Yanhua; Zhang, Yawei; Tang, Weizhong (Frontiers in Oncology, 2021)
Purpose This study aimed to elucidate the prognostic significance of a novel inflammation-joined and nutrition-related clinicopathological marker for colorectal cancer (CRC). Methods Various factors from preoperative fasting blood samples from 2471 patients with CRC were retrospectively analyzed. Factors related to prognosis were evaluated using univariate and multivariate analyses. The Kaplan–Meier method was used to generate survival curves, while the log-rank test was used to measure survival differences between groups. Results Univariate analysis revealed that C-reactive protein (CRP)/mean corpuscular volume (MCV) ratio, TNM stage, differentiation, right-sided tumor, age, carcinoembryonic antigen (CEA) level, and CRP level were significantly associated with poor prognosis in CRC. In contrast, adjuvant chemotherapy is regarded as a protective factor. Elevation of CRP/MCV ratio (odds ratio [OR]: 1.535, 95% confidence interval [CI]: 1.121–2.104, P = 0.008), TNM stage (OR: 2.747, 95% CI: 2.175–3.469, P < 0.001), and differentiation (OR, 1.384; 95% CI, 1.150–1.666; P = 0.001) were prognostic risk factors in the multivariate analyses. Subgroup analysis showed that CRP/MCV, TNM staging system, and differentiation also independently affected survival in patients with lymph node-positive CRC. The nomogram based on these three indicators showed that CRP/MCV had a greater prognostic value and clinical significance for lymph node-positive patients with poorly differentiated tumors at the late stage. Conclusion A novel nomogram using the clinicopathologic index of inflammation and nutrition was constructed to predict the prognosis of CRC. Early interventions should be emphasized for advanced-stage patients with severe inflammation and poor nutritional status.